2015
DOI: 10.1371/journal.pone.0137468
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of a Novel Mitochondrially-Encoded Gene in Gonadic Precursors May Drive Paternal Inheritance of Mitochondria

Abstract: Mitochondria have an active role in germ line development, and their inheritance dynamics are relevant to this process. Recently, a novel protein (RPHM21) was shown to be encoded in sperm by the male-transmitted mtDNA of Ruditapes philippinarum, a species with Doubly Uniparental Inheritance (DUI) of mitochondria. In silico analyses suggested a viral origin of RPHM21, and we hypothesized that the endogenization of a viral element provided sperm mitochondria of R. philippinarum with the ability to invade male ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 73 publications
6
53
1
Order By: Relevance
“…Likewise, Obata et al (2010) identified vasa-positive cells in Mytilus galloprovincialis, again suggesting the existence of GSCs in connective tissue during the non-reproductive season in mussel. Interestingly, as will be further discussed below, Milani et al (2015Milani et al ( , 2017 confirmed through confocal microscopy that Vasa is a germ cell marker in several species of bivalve.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Likewise, Obata et al (2010) identified vasa-positive cells in Mytilus galloprovincialis, again suggesting the existence of GSCs in connective tissue during the non-reproductive season in mussel. Interestingly, as will be further discussed below, Milani et al (2015Milani et al ( , 2017 confirmed through confocal microscopy that Vasa is a germ cell marker in several species of bivalve.…”
Section: Introductionmentioning
confidence: 68%
“…Gametogenesis has long been of interest in bivalves (reviewed in Galtsoff, 1964), and has received renewed attention following the development of genomics in bivalves (Fabioux et al, 2004a(Fabioux et al, ,b, 2009Llera-Herrera et al, 2013;Milani et al, 2015Milani et al, , 2017Obata et al, 2010;Teaniniuraitemoana et al, 2017) and, more recently, because of current environmental concerns (Barranger et al, 2014;Cubero-Leon et al, 2012;de Sousa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For histological sample preparation, the entire body was processed for hematoxylin and eosin staining following the method in Bettini et al [17]. Tissue samples for immunohistochemistry were processed as described in Milani et al [18] with the following modifications: the entire body was collected from animals in the spent phase and fixed for 3.5 hours, while, given their larger body dimensions, pieces of the body of about 0.5-0.8 cm 3 were sampled from specimens in the gametogenic phase (July 2015-2016) and fixed for 3 hours. Details on antisera production as well as specificity tests and experimental controls are provided in Milani et al [18].…”
Section: Methodsmentioning
confidence: 99%
“…ggplot2 is an implementation of The Grammar of Graphics (Wilkinson 2005) and rigorously enforces Wilkinson's series of grammatical rules for creating perceivable graphs, therefore, by using ggplot2 as a basis for the present work, we inherit this compelling philosophy, perhaps, from time-to-time, allowing the user to create graphical poetry (Wickham 2010). Under peer-review, ggtern has already been utilized in various publications and fields, including for example, works by Witte, Bradley, Enright, and Muljo (2015), Milani, Ghiselli, Pecci, Maurizii, and Passamonti (2015); Wenger, Buzgariu, and Galliot (2016); Kalenitchenko et al (2016); Chu, Ma, Prince, Antony, Seferovic, and Aagaard (2017) and Nesbitt et al (2017).…”
Section: Introductionmentioning
confidence: 99%